PS-R01-7: A CASE REPORT OF ACCELERATED-MALIGNANT HYPERTENSION SUCCESSFULLY TREATED WITH SACUBITRIL/VALSARTAN. (January 2023) - Morita, Ryutaro; Azushima, Kengo; Urate, Shingo; Ebihara, Masayuki; Kinguchi, Sho; Kanai, Daisuke; Kanaoka, Tomohiko; Wakui, Hiromichi; Toya, Yoshiyuki; Tamura, Kouichi
Abstract : Angiotensin receptor-neprilysin inhibitor (ARNI) is an emerging therapeutic strategy for cardiorenal syndrome. Although the treatment with ARNI for hypertension is covered by governmental insurance systems in Japan, a putative position of ARNI in clinical hypertension guidelines is yet to be determined. However, clinical and experimental evidence is now accumulating concerning the therapeutic effects of ARNI for hypertension, in addition to heart failure, in Japan. Here we would like to present a case in which treatment with ARNI for hypertension was effective to beneficially control cardiorenal syndrome as well as hypertension. A 51-years-old man with a history of hypertension since 35 years-old experienced shortness of breath on exertion and on supine position visited Yokohama City University Hospital. Severely elevated blood pressure (234/165 mmHg) with hypertensive retinopathy (Keith-Wagner IIb, Scheie S2H3), as well as cardiorenal dysfunction (LVEF 39% on UCG, eGFR 25.4 mL/min/1.73m2, UPCR 0.56 g/gCr), were noted, and he was admitted to the hospital due to accelerated-malignant hypertension. On admission, the patient was administered with intravenous nicardipine to achieve blood pressure level around 160/110 mmHg, and then treated with oral nifedipine (40–80 mg daily) with tapering of intravenous nicardipine administration. After treatment transition to single oral nifedipine therapy (80 mg daily), his blood pressure was still around160/110 mmHg. Thus, treatment with ARNI (sacubitril/valsartan) was initiated with a starting dose of 50 mg daily on Day 9. On Day 10, his blood pressure was improved to around 130/90 mmHg without evident worsening of kidney function or elevation of serum potassium level. The patient was successfully treated with appropriate control of blood pressure without initiation of dialysis. This case suggests that ARNI is an interesting therapeutic strategy to treat cardiorenal syndrome with severe hypertension.